2021
DOI: 10.26868/25222708.2021.30583
|View full text |Cite
|
Sign up to set email alerts
|

Validation of spectral simulation tools for the prediction of indoor daylight exposure

Abstract: A growing area of research focuses on the relationship between ocular light exposure and the non-visual responses. In order to accelerate research on this topic and improve building design, reliable spectral simulation tools are needed. This study aims at validating two of them, Lark and ALFA, by comparing their outcomes against daylight measurements. The goal is to assess how reliable these tools are in predicting spectral irradiance under different skies for indoor spaces. While spectral irradiance can in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…This error margin is consistent with our findings for all channels in the daylight scenario. 18 However, as our physical model was considerably simpler than that of the above-referenced study, we presume that this is the reason for the lower error in our results.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This error margin is consistent with our findings for all channels in the daylight scenario. 18 However, as our physical model was considerably simpler than that of the above-referenced study, we presume that this is the reason for the lower error in our results.…”
Section: Discussionmentioning
confidence: 65%
“…To our knowledge, only a limited number of studies investigated spectral simulations for daylighting. 17,18 Moreover, no studies that validate the N -step algorithm for the combination of daylighting and electric lighting were found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…One study found that Lark calculates spectral irradiance with most errors within a ±20% range in a neutrally coloured space under daylight. 78 The authors noted a reproducibility error in ALFA , unresolved at the time of their study. It was also shown that under clear sky conditions ALFA tends to overestimate the irradiance, 99 even though the spectral characteristics are well represented.…”
Section: Resultsmentioning
confidence: 96%
“…The 9-channel results of the 3 Radiance simulations are used by Lark 2.0 to derive the average spectral irradiance over each channel (Pierson et al, 2021). The spectral irradiance is extrapolated for every nanometer, assuming that it is constant within each channel and equal to the average.…”
Section: Spectral Irradiancementioning
confidence: 99%
“…Since Radiance performs simulations with a 3-channel resolution, Lark combines the results of three individual simulations, each for different parts of the visible spectrum. Validation studies showed that this approach can predict spectral irradiance indoors with a reasonable accuracy (most errors are within a ±20% range compared to physical measurements) under daylight conditions (Pierson et al, 2021). Although Lark offered the possibility to include spectral composition with a 9-channel resolution in lighting design, until now it did not allow to analyse the spatial and temporal characteristics of light.…”
Section: Introductionmentioning
confidence: 99%